2022
DOI: 10.1039/d2ta06692k
|View full text |Cite
|
Sign up to set email alerts
|

Upcycling waste poly(ethylene terephthalate) into polymer electrolytes

Abstract: Lithium-ion batteries (LiB) play an important role for energy storage in our increasingly-electrified modern world, with polymer electrolyte (PE) materials poised to revolutionise battery design by eliminating the most critical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Indeed, polyurethanes synthesized from PET-derived BHETA have recently been shown to be useful as polymer electrolytes for energy storage in prototype lithium-ion batteries. 96 Glycolysis, alcoholysis, and aminolysis are facilitated by different classes of catalysts, such as Lewis acid metal complexes such as aluminum triisopropoxide 97 and dibutyltin oxide, 98 deepeutectic solvents (e.g., 1,3-dimethylurea/zinc acetate) 99 and organocatalysts (e.g., 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) 100 ). More recently, Jehanno et al 101 demonstrated a sustainable PET chemical recycling process using an ionic salt comprising TBD and methanesulfonic acid (MSA).…”
Section: Polyetheretherketone (Peek)mentioning
confidence: 99%
“…Indeed, polyurethanes synthesized from PET-derived BHETA have recently been shown to be useful as polymer electrolytes for energy storage in prototype lithium-ion batteries. 96 Glycolysis, alcoholysis, and aminolysis are facilitated by different classes of catalysts, such as Lewis acid metal complexes such as aluminum triisopropoxide 97 and dibutyltin oxide, 98 deepeutectic solvents (e.g., 1,3-dimethylurea/zinc acetate) 99 and organocatalysts (e.g., 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) 100 ). More recently, Jehanno et al 101 demonstrated a sustainable PET chemical recycling process using an ionic salt comprising TBD and methanesulfonic acid (MSA).…”
Section: Polyetheretherketone (Peek)mentioning
confidence: 99%
“…2). In catalysis, the complete C–X/C–C bond cleavage requires homogenous organocatalysts 37,38 or complex heterogeneous catalytic systems utilising rare-earth metals ( e.g. , Pd and Ru) along with expensive ligands 39,40 and long reaction period to attain high conversion and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…2). In catalysis, the complete C-X/C-C bond cleavage requires homogenous organocatalysts 37,38 or complex heterogeneous catalytic systems utilising rare-earth metals (e.g., Pd and Ru) along with expensive ligands 39,40 and long reaction period to attain high conversion and selectivity. Despite catalytic fundamentals being important, post-polymerisation modification and surface chemistry principles are dominant for functional upcycling (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Even though mechanical recycling of PS can be performed commercially, the inevitable material degradation during repeated recycling will eventually relegate the polymers for the same end-of-life disposal. Chemical recycling and upcycling have recently emerged as promising alternatives for post-use treatment of PS waste, though additives in these plastics, such as dyes, may hinder the chemical process. , For instance, pyrolysis allows the recovery of the styrene monomer, benzene, and other alkylaromatics, though these processes are highly energetically demanding and give complex product mixtures which are difficult to separate. , Recent efforts in chemical upcycling of waste PS include transformations to functional materials, such as catalysts, flocculating agents, and fluorescent sensors for cations, , as well as conversion to valuable small aromatic molecules, including arylamines, oxygenated aromatics, and aromatic hydrocarbons (e.g., toluene and biphenyl) . These valorization efforts contribute toward creating a circular plastics economy by utilizing waste plastics as an abundant, low-cost feedstock…”
Section: Introductionmentioning
confidence: 99%